Neuroimaging of brain connectivity related to reading outcomes in children born preterm: A critical narrative review - Kelly, Kaitlyn J.; Hutton, John S.; Parikh, Nehal A.; Barnes-Davis, Maria E. (Frontiers in Pediatrics, 2023)
Premature children are at high risk for delays in language and reading, which can lead to poor school achievement. Neuroimaging studies have assessed structural and functional connectivity by diffusion MRI, functional MRI, and magnetoencephalography, in order to better define the “reading network” in children born preterm. Findings point to differences in structural and functional connectivity compared to children born at term. It is not entirely clear whether this discrepancy is due to delayed development or alternative mechanisms for reading, which may have developed to compensate for brain injury in the perinatal period. This narrative review critically appraises the existing literature evaluating the neural basis of reading in preterm children, summarizes the current findings, and suggests future directions in the field.